(untitled) (Research, Society and Development, 2021)
Currently, there is a great search for alternative therapies, both by dentists and patients. In the midst of several options, there is acupuncture, a technique that is part of Traditional Chinese Medicine, which consists of the insertion of needles, in specific points of the skin, along the body. This technique has scientifically proven its capacities, anxiolytic, hemostatic, anti-inflammatory, analgesic, myo-relaxing and activating the immune function. It is proving to be an extremely interesting alternative for both the patient and the dental surgeon, since it provides safety and comfort for both. This work aims to group information on the benefit of acupuncture within dentistry and expose it in a didactic way to professionals in this area, thus expanding their horizon of knowledge and enabling them to offer this alternative to patients and increasing thus the range of options for these. A narrative literature review of the theme was carried out, using as a reference base 20 articles available on online platforms, such as VHL salud, Scielo and Pubmed. Articles in Portuguese and English were used.